Internal Supervision and Learning Management on the Multicultural Society Curriculum of Schools under the Office of Private Education in the Three Southern Border Provinces - ปิริยะ, บุศรินทร์ (วารสาร อัล-ฮิกมะฮฺ, 2022)
The objectives of this research were 1) to study the level of internal supervision of school administrators. under the Office of Private Education in the three southern border provinces 2) to study the level of learning in the multicultural society curriculum of teachers in schools under the Office of Private Education in the three southern border provinces 3) to compare the internal supervision of school administrators under the Office of Private Education in the three southern border provinces, classified by gender, age, educational background, work experience and school size 4) to compare the learning management of the multicultural society curriculum of teachers in schools under the Office of Private Education in the three southern border provinces, classified by gender, age, educational background, work experience and the size of the school 5) To study the relationship between internal supervision and learning management of the multicultural society curriculum of schools under the Office of Private Education. in the three southern border provinces; 6) to compile recommendations on internal supervision and learning management of the multicultural society curriculum of schools under the Office of Private Education. in the three southern border provinces The sample group consisted of teachers working in pilot schools for implementing multicultural society curriculum in learning management under the Office of Private Education. In the three southern border provinces of the 17 provinces of 324 people, the sample size was determined by comparison with the Craigcy and Morgan tables (Krejcie and Morgan, 1970: 607-610) and selected samples by using a simple random sampling method with picking up labels without replacing (Without Replacement). The instrument used in the research was a questionnaire divided into 5 parts. The statistics used were frequency values, hundred values. each arithmetic mean Standard deviation, t-test, F-test, when the difference was found, the test was used. using the chef's method and Pearson's correlation coefficient The results showed that The level of internal supervision of school administrators under the Office of Private Education in the three southern border provinces Overall, it's at a high level. The level of learning management in the multicultural society curriculum of schools under the Office of Private Education in the three southern border provinces Overall, it's at a high level. Comparison of differences in internal supervision of school administrators under the Office of Private Education in the three southern border provinces, classified by gender, age, educational background, work experience and the size of the school found that overall and each aspect was not different 4.Comparison of the level of learning management in the multicultural society curriculum of teachers in schools under the Office of Private Education in the three southern border provinces classified by gender, age, educational background, work experience and the size of the school found that overall and in each aspect were not different. Relationship between internal supervision and learning management in multicultural society of schools under the Office of Private Education In the three southern border provinces, it was found that, overall, there was a positive relationship. is at a relatively high level statistically significant at the .01 level 6.Suggestions include administrators are important mechanisms for successful school administration. The results of learning management and activities of teachers must be monitored in order to collect problems and obstacles that affect learning management. Taking care of subordinates send teachers to participate in professional development Teachers need to manage learning by integrating the body of knowledge in order for children to create truly desirable knowledge and skills equally. Keywords: Internal Supervision; Learning Management on the Multicultural Society Curriculum